2002
DOI: 10.1080/074811802760138996
|View full text |Cite
|
Sign up to set email alerts
|

Grief Work Versus Continuing Bonds: A Call for Paradigm Integration or Replacement?

Abstract: In this paper we compare grief work and continuing bond models of grief to determine if one explains the data better than the other. Sixty individuals in active grief completed a questionnaire in which they were asked to rate their grief status, perceived similarity to the deceased along 7 dimensions, and closeness of relationship to the deceased. A matched control group was also asked to rate the closeness of relationship and perceived similarity to a living person of the same relationship as the deceased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 5 publications
1
11
1
3
Order By: Relevance
“…The fact that both themes were frequently coded in the same respondent, and even response, can be seen in theory as an inconsistency with that professional stock, but could also indicate that both are being used in a complementary way by the clinician practising in situ . This latter interpretation of our finding would resonate with the ideas of Russac, Steighner and Canto (2002) and Stroebe and Schut (2005), who argued for the need to integrate these two hypotheses.…”
Section: Discussionsupporting
confidence: 89%
“…The fact that both themes were frequently coded in the same respondent, and even response, can be seen in theory as an inconsistency with that professional stock, but could also indicate that both are being used in a complementary way by the clinician practising in situ . This latter interpretation of our finding would resonate with the ideas of Russac, Steighner and Canto (2002) and Stroebe and Schut (2005), who argued for the need to integrate these two hypotheses.…”
Section: Discussionsupporting
confidence: 89%
“…This type of experience has also been described in a case of grief resolved spontaneously under an altered state of consciousness induced with ketamine (Gowda et al, 2016). Attachment theory (Bowlby, 1977) and the construct of continuing bonds (Field, 2006;Russac, Steighner, & Canto, 2002) are an underlying component of bereavement and an important element of coping with the grief (Barrera et al, 2009;Darbyshire et al, 2013;Klass, 2006;Neimeyer, 2006). Furthermore, these experiences permit the resolution of outstanding issues, such as saying goodbye to the loved one or communicating matters that were left unsaid.…”
Section: Qualitative Findingsmentioning
confidence: 84%
“…However, this notion has been challenged (e.g., Klass, 1993;Murphy, Johnson, Chung, & Beaton, 2003). In one such study, Russac, Steighner, and Canto (2001) questioned a group of bereaved college students about their sense of closeness to the deceased person. They found that although mean ratings of closeness decreased over the time after the loss, there was no difference at end point between the bereaved students and a non-bereaved control group matched for the same relationship.…”
Section: Bereavement and Attachmentmentioning
confidence: 97%